Innovation in the Malaysian furniture industry: drivers and challenges - Ratnasingam, Jegatheswaran; Chin, Khoon Ark; Ab Latib, Hazirah; Subramaniam, Hasshviny; Khoo, Albert (North Carolina State University, 2018)
The Malaysian furniture industry is the country’s fastest growing sub-sector within the wood-based industry, and its socio-economic importance cannot be taken lightly. The industry is driven primarily by comparative advantages derived from low cost factor inputs, which has eroded in recent years due to escalating production cost. Further, the increasing competition from other cheaper producing nations, particularly China and Vietnam, is also putting a damper on the future competitiveness of the industry in Malaysia. To remain competitive, the Malaysian furniture industry must transform and advance the value-chain through innovation and value-addition. Although the government has played a pivotal role in providing a broad policy framework to support value-adding and innovative activities, success has been limited. This study evaluated the extent of innovation and its sources in the Malaysian furniture industry through an internet-based survey. The results indicated that external sources of innovation were more important than internal sources. The factor analysis showed that external inputs, market demand, and in-house research and development were the most important drivers of the innovation in the Malaysian furniture industry. Therefore, the furniture industry in Malaysia will require policy support to enhance its inherent capability for innovation in the long-term.